REDESAIN LABEL KEMASAN KUE BASAH BERBASIS INTELLIGENT PACKAGING DENGAN PENDEKATAN KANSEL ENGINEERING : STUDI KASUS TOKO KUE BUNDA RAYYA - arief marna Sonjaya sonjaya; Melati Pratama (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2026)
Bunda Rayya is a cake shop in Palembang that produces wet cakes with a short shelf life, requiring packaging redesign to improve product information and quality. This study aims to identify relevant Kansei elements, redesign the packaging label using intelligent packaging features, and assess consumer preferences. A quantitative approach was applied by distributing questionnaires to 67 respondents in the first stage and 50 in the second stage. The results indicate that the key Kansei elements include attractive colors, distinctive design, thick packaging material, clear typography, and expiration information. Two redesigned label concepts were developed, and Design 1 received the highest preference, particularly in color (3.89), distinctive design (3.95), typography (4.28), and expiration information (3.72).